Tubulin-Targeting Activity Of Phytoestrogens Present In Cosmos Caudatus Aqueous Extract Against Colorectal Cancer Cell Line Ht-29 - Xu, Fan (2023)
Cosmos caudatus (C. caudatus) is a medicinal plant in Southeast Asia that contains phytoestrogens, sesquiterpene lactones and essential micronutrients. Phytoestrogens have been reported to possess pharmacological properties including anticancer activity. In this study we aimed to investigate tubulin-targeted activity of main phytoestrogens present in C. caudatus along with C. caudatus aqueous extract in colorectal cancer cell line HT-29. C. caudatus aqueous extract, kaempferol and quercetin were used to treat HT-29 cells for 24, 48 and 72 hours in 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay to evaluate the effects of the treatments on cell viability.